PTU-050 Patients with interval colorectal cancers(crc) 'missed' on the national faecal occult blood (fob) screening programme have a worse outcome in the short-term compared to patients who declined to join the programme – results from a multicentre study. (17th June 2017) - George, AT; Aggarwal, S; Dharmavaram, S; Menon, A; Dube, M; Vogler, M; Field, A
Abstract : Introduction: To compare outcomes of the two groups Method: National Bowel Cancer Audit Programme data from three centres, for all colorectal cancers(CRC)in the screening age group(60–74 years)over a 2 year period(August 2011–2013)were linked for their Faecal Occult Blood Testing(FOBT)screening status( BCSP database/Eastern Hub ).Patient/tumour demographics and survival for Interval cancers(IC-screening patients developing cancers within 2 years of a negative FOB test)and cancers in those who declined the screening programme were analysed.All three centres were in incident rounds of screening.Tumours at and beyond splenic flexure were considered left-sided. 1 year mortality was looked at as all patients had a minimum of 1 year follow-up. Results: Of the 521 CRC identified, 127 (25%)were IC and 228 (44%)were cancers in the declined screening group.The mean age at cancer diagnosis(66.8 years vrs 67.5 years;p =0.014, X 2 = 0.33 );male:female ratio(83:44 vrs 130:98; p =0.024, X 2 = 2.36 )and ethnic demographics(white british:others;123:5vrs211:20; p =0.090, X 2 = 2.87 )between the IC and declined screening groups were comparable.Between the IC and Declined Screening groups, the tumour location( right-sided:left-side d;48:79 vrs 66:162; p =0.024, X 2 = 2.36 )and polyp:non-polyp cancers(2:125 vrs 1:227; p =0.262, X 2 = 1.25 )were comparable. The IC had a higher proportion of advanced cancers at presentation(Dukes C/D;89 (70%)vs122(53%);p = 0.002, X 2 = 9.28 )compared to the declined screening group. Mortality-data: 1 year mortality was 20 (16%)and 25 (11%)for the IC and declined screening groups respectively.There was no gender, age or ethnic differences between the two groups.The mortality of right-sided cancers in the IC group was significantly higher than that for the declined screening group(10 (21%) vrs 4 (6%);p = 0.037, X 2 = 4.32 ) . Conclusion: Our findings highlight that patients on the national FOBT screening programme who develop IC (specially right-sided)fared worse in the short-term, compared to CRC in patients who had declined FOBT screening-due to a higher tumour stage and a higher 1 year mortality. Disclosure of Interest: None Declared